2016
DOI: 10.1016/j.clinthera.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cefoxitin Plasma and Subcutaneous Adipose Tissue Concentration in Patients Undergoing Sleeve Gastrectomy

Abstract: Purpose Antibiotic dosing in obese surgical patients has not been adequately evaluated. Cefoxitin is an antibiotic commonly utilized for surgical prophylaxis in cases involving the abdominal cavity. The objective of our study was to identify whether currently prescribed doses of cefoxitin achieve adequate and sustained plasma and tissue concentrations in obese patients undergoing sleeve gastrectomy Methods A prospective evaluation of plasma and tissue cefoxitin concentrations in patients undergoing sleeve ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a study by Toma et al [13] , adipose tissue cefoxitin concentrations in obese patients undergoing abdominal and pelvic surgery were below the minimum inhibitory concentration (MIC) despite giving twice the normal dose. Similarly, Brunetti et al [14] reported that subcutaneous adipose tissue concentrations of cefoxitin at the time of surgical closure were subtherapeutic in six patients undergoing sleeve gastrectomy. Moine showed that a single dose of cefoxitin at 40 mg/kg failed to achieve the desired probability of target attainment in fat tissue for Staphylococcus aureus, Escherichia coli, and Bacteroides fragilis over 4-h periods postdose [15] .…”
Section: Obesitymentioning
confidence: 88%
“…In a study by Toma et al [13] , adipose tissue cefoxitin concentrations in obese patients undergoing abdominal and pelvic surgery were below the minimum inhibitory concentration (MIC) despite giving twice the normal dose. Similarly, Brunetti et al [14] reported that subcutaneous adipose tissue concentrations of cefoxitin at the time of surgical closure were subtherapeutic in six patients undergoing sleeve gastrectomy. Moine showed that a single dose of cefoxitin at 40 mg/kg failed to achieve the desired probability of target attainment in fat tissue for Staphylococcus aureus, Escherichia coli, and Bacteroides fragilis over 4-h periods postdose [15] .…”
Section: Obesitymentioning
confidence: 88%
“…Interestingly, after systemic administration at the usual dose (2 g) in patients, FOX total plasma concentrations reach values of up to 200 mg/liter (23), which, considering that the unbound fraction is close to 25% (24), corresponds to maximum unbound plasma concentrations on the order of 50 mg/liter. In this range of values, unbound FOX concentrations should demonstrate antimicrobial efficacy only against the susceptible M. abscessus population.…”
Section: Cefoxitin Nebulization Against Mycobacterium Abscessusmentioning
confidence: 99%
“…[14][15][16][17][18][19] A simple liquid chromatography method with UV detection has been developed and fully validated for the determination of cefazolin in human plasma. [14][15][16][17][18][19] A simple liquid chromatography method with UV detection has been developed and fully validated for the determination of cefazolin in human plasma.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed several chromatographic methods with ultraviolet (UV) detection that focuses on the determination of cephalosporins in biofluids. [14][15][16][17][18][19] A simple liquid chromatography method with UV detection has been developed and fully validated for the determination of cefazolin in human plasma. [20] In addition, hyphenated techniques, such as liquid-chromatographytandem mass spectrometry (LC-MS/MS) have also been applied for the determination of cefazolin in human plasma using solidphase extraction (SPE) for sample preparation [21,22] and in human plasma and subcutaneous interstitial fluid of patients undergoing elective/semi-elective abdominal aortic aneurysm open repair surgery, [23] cefuroxime sodium in human plasma or serum [24,25] and cefuroxime lysine in rat brain [26] and in dog plasma.…”
Section: Introductionmentioning
confidence: 99%